Osmotic stress and recovery in field populations of Zygnema sp. (Zygnematophyceae, Streptophyta) on Svalbard (High Arctic) subjected to natural desiccation. Issue 2 (19th February 2014) - Pichrtová, Martina; Hájek, Tomáš; Elster, Josef
Abstract Zygnema is a genus of filamentous green algae belonging to the class of Zygnematophyceae (Streptophyta). In the Arctic, it typically forms extensive mats in habitats that regularly dry out during summer, and therefore, mechanisms of stress resistance are expected. We investigated its natural populations with respect to production of specialized desiccation‐resistant cells and osmotic acclimation. Six populations in various stages of natural desiccation were selected, from wet biomass floating in water to dried paper‐like crusts. After rewetting, plasmolysis and osmotic stress effects were studied using hypertonic sorbitol solutions, and the physiological state was estimated using chlorophyll a fluorescence parameters. All populations of Zygnema sp. formed stationary‐phase cells filled with storage products. In green algal research, such cells are traditionally called akinetes. However, the populations differed in their reaction to osmotic stress. Whereas the wet‐collected samples were strongly impaired, the osmotic stress resistance of the naturally dried samples was comparable to that of true aeroterrestrial algae. We showed that arctic populations of Zygnema acclimate well to natural desiccation via hardening that is mediated by slow desiccation. As no other types of specialized cells were observed, we assume that the naturally hardened akinetes also play a key role in winter survival.